2019
DOI: 10.1186/s13071-019-3540-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of human head lice and molecular detection of associated bacterial pathogens in Democratic Republic of Congo

Abstract: Background Head louse, Pediculus humanus capitis , is an obligatory blood-sucking ectoparasite, distributed worldwide. Phylogenetically, it occurs in five divergent mitochondrial clades (A–E); each exhibiting a particular geographical distribution. Recent studies suggest that, as in the case of body louse, head louse could be a disease vector. We aimed to study the genetic diversity of head lice collected in the Democratic Republic of the Congo (DR Congo) and to screen f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 50 publications
1
21
0
1
Order By: Relevance
“…This individual could have been in close contact with a person returning from Mali and infested with head lice. Clade E had been recently described in head lice of women from DR Congo [15], but it is frequently identified in West African countries (Mali and Senegal) [17].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This individual could have been in close contact with a person returning from Mali and infested with head lice. Clade E had been recently described in head lice of women from DR Congo [15], but it is frequently identified in West African countries (Mali and Senegal) [17].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that these species have a low prevalence rate and are less resistant and virulent than A. baumannii [41]. Finally, several species of the genus Acinetobacter have been reported in head lice collected worldwide, particularly in Africa [15,22,28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations